Cuba and the Secret World. Issue 1 (2nd January 2021) - Lockhart, James
Abstract: This article explores the career of Maj. Juan Rodríguez, who served in Cuban intelligence from 1958 to 1987. It discusses the origins and nature of the Castro regime's security and intelligence services, including the development and prioritization of their missions. It identifies the milestones that defined these services' institutional history. It connects this history to US–Cuban relations in the post-Cold War period. And it proposes a research agenda that will contribute to more equitable and integrated approaches to the modern and contemporary history of the Americas and the developing world, and to more diverse and representative security and intelligence studies.